A rational approach to form disulfide linked mucin hydrogels. Issue 47 (25th October 2019) - Joyner, Katherine; Song, Daniel; Hawkins, Robert F.; Silcott, Richard D.; Duncan, Gregg A.
Abstract : In this work, we demonstrate how crude mucins, incapable of forming gels, may be restored to behave like natural mucus. Abstract : We report the design of a mucin hydrogel created using a thiol-based cross-linking strategy. By using a cross-linking reagent capable of forming hydrogen bonds and disulfide linkages within the gel network, we were able to produce mucin-based hydrogels with viscoelastic properties similar to natural mucus as measured by bulk rheology. We confirmed disulfide cross-links strongly contribute to gel formation in our system using chemical treatments to block and reduce cysteines where we found mucin hydrogel network formation was inhibited and disrupted, respectively. Particle tracking microrheology was used to investigate the kinetics and evolution of microstructure and viscoelasticity within the hydrogel as it formed. We found that the rate of gel formation could be tuned by varying the mucin to crosslinker ratio, producing network pore sizes in the range measured previously in human mucus. The results of this work provide a new, simple method for creating mucin hydrogels with physiologically relevant properties using readily available reagents.